eCM 2013
DOI: 10.22203/ecm.v025a06
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate reduced peri-tunnel bone loss and enhanced tendon graft to bone tunnel healing in anterior cruciate ligament reconstruction

Abstract: Peri-tunnel bone loss after anterior cruciate ligament (ACL) reconstruction is commonly observed, both clinically and experimentally. We aimed to study the effect and mechanisms of different doses of alendronate in the reduction of peritunnel bone loss and promotion of graft-bone tunnel healing in ACL reconstruction. Eighty-four ACL-reconstructed rats were divided into 4 groups. Alendronate at different dosages, or saline, were injected subcutaneously weekly, for 2 or 6 weeks post-reconstruction, for vivaCT (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
72
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 43 publications
2
72
1
Order By: Relevance
“…MMPs expression increased in the ACL itself after ACL injury [27]. Therefore, the graft bone tunnel healing could be improved by inhibiting MMPs expression [28]. The increase in MMP expression in the ligament is consistent with prior report that levels of MMP-1 and MMP-3 in the knee were significantly higher, suggesting that increased levels of both enzymes in the knee indicate enhanced severity of synovial inflammation and also accelerated activity of joint destruction [29].…”
Section: Discussionsupporting
confidence: 81%
“…MMPs expression increased in the ACL itself after ACL injury [27]. Therefore, the graft bone tunnel healing could be improved by inhibiting MMPs expression [28]. The increase in MMP expression in the ligament is consistent with prior report that levels of MMP-1 and MMP-3 in the knee were significantly higher, suggesting that increased levels of both enzymes in the knee indicate enhanced severity of synovial inflammation and also accelerated activity of joint destruction [29].…”
Section: Discussionsupporting
confidence: 81%
“…We managed this issue by having 2 experienced investigators performing all the surgical procedures according to the published standardized protocol. 14,15 The tendon graft was fixed to the femoral and tibial tunnel exits by suturing to the neighboring periosteum. However, the tendon graft is secured by interference screws, endobuttons, or staples in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…investigated the effects of systematic administration of alendronate on the healing of tendon-bone interface in a rat ACL reconstruction model. Results showed that alendronate treatment reduced the expression of MMP1, MMP3 and CD68-positive cells (CD68: marker for the various cells of the macrophage lineage, including osteoclasts precursors and osteoclasts) at the region of peri-tunnel region as well as the interface of graft-bone tunnel (59). In addition, Lui et al .…”
Section: Small Molecule Mediated Ligament Formationmentioning
confidence: 99%